Tamil Insights: Enhancing Oral Health Education (OHE) Through Questionnaire Validation - M Anita; S Bhuminathan; V Priya; R Pradeep Kumar; P Suganya; Charumathi Dhanushkodi (Journal of Pharmacy and Bioallied Sciences)
Aim: This study aims to validate an OHE questionnaire in Tamil to ensure linguistic and cultural accuracy for Tamil-speaking populations. Methodology: The study involved English-Tamil fluent adults, using a 15-item OHE questionnaire translated through expert forward and backward translations. An expert panel ensured conceptual equivalence, and a pilot study with 30 participants refined the translation. The final Tamil version was tested for internal consistency with 1500 participants and test-retest reliability with 500 persons. Results: The Tamil OHE questionnaire demonstrated excellent internal consistency, with Cronbach’s alpha values >0.99, and high test-retest reliability, with Pearson correlation coefficients >0.90 for most items. Conclusion: The validated Tamil OHE questionnaire is a reliable tool for evaluating oral health-related quality of life, supporting effective, and culturally appropriate oral health interventions in Tamil-speaking regions.